2020
DOI: 10.1093/ehjqcco/qcaa011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of long-term mortality between living alone patients vs. living together patients with acute coronary syndrome treated with percutaneous coronary intervention

Abstract: Aims Living alone is reported as an independent risk factor for cardiovascular disease. However, little is known about the association between clinical outcomes and living alone in patients with acute coronary syndrome (ACS). The aim of this study was to determine whether living alone is an independent prognostic risk factor for long-term mortality stratified by age in patients with ACS who were treated with primary percutaneous coronary intervention (PCI). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…5 8 In the current study, females were more common in ACS patients living alone than those living with others, and those living alone were older, as seen in previous studies, suggesting that ACS patients living alone is essential problems in aging society. 4 5 6 7 9 11 22 23 Similarly to previous studies, 5 6 7 8 9 10 11 23 the current study shows that living alone, compared with living with others, is a predictor of cardiac mortality in 2 years. In recent years, due to the diversification of social lifestyles, common-law partners are becoming more common.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…5 8 In the current study, females were more common in ACS patients living alone than those living with others, and those living alone were older, as seen in previous studies, suggesting that ACS patients living alone is essential problems in aging society. 4 5 6 7 9 11 22 23 Similarly to previous studies, 5 6 7 8 9 10 11 23 the current study shows that living alone, compared with living with others, is a predictor of cardiac mortality in 2 years. In recent years, due to the diversification of social lifestyles, common-law partners are becoming more common.…”
Section: Discussionsupporting
confidence: 87%
“…Previous reports have compared clinical background (age, gender, preexisting coronary risk factors, and clinical severity) for each type of living arrangement. Although no definitive conclusions have been reached, there are some reports that the frequency of diabetes, 4 7 hypertension, 5 10 11 and dyslipidemia 10 is higher in the group living alone than in the group living with others, suggesting that arteriosclerosis may be more advanced in the group living alone. However, morphology of coronary artery culprit lesions evaluated by intravascular imaging has not yet been compared between ACS patients living alone and those living with others.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Living alone was found to be associated with higher mortality rates in young patients with acute coronary syndromes. 31 The cost of tablets for 1 week can create a significant burden on hospital budgets. In our HMO-based integrated hospital-community system, this also requires budgetary dialog between stakeholders, 32 namely, the hospital and the community administration of the same HMO.…”
Section: Discussionmentioning
confidence: 99%
“…Early primary percutaneous coronary intervention (PPCI) has been established as the first-line treatment for patients with acute myocardial infarction (MI). 1 A randomized trial of moderate size [2][3][4][5][6][7] showed a significant increase in major adverse cardio cerebral events (MACCE) post PPCI. Indeed, residual atherothrombotic risk remains substantial in high-risk patients and lesion subsets, including those older than 65 years, with renal dysfunction, diabetes mellitus (DM), thrombotic target lesions, and multi-vessel disease.…”
Section: Introductionmentioning
confidence: 99%